Effect of 'Jamblang' (Syzygium cumini) Peel and Citric Acid Addition on Antioxidant Activity of 'Kolang-kaling' Jam - Anggraini, Tuty; Kurniawan, Yulita; Yenrina, Rina; Sayuti, Kesuma (Pakistan Journal of Nutrition, 2018)
Background and Objective: The addition of ‘jamblang’ peel could increase the beneficial properties of ‘Kolang-kaling’ jam, including antioxidant activity. This study was conducted to evaluate the effect of ‘jamblang’ peel and citric acid addition on the antioxidant activity of ‘Kolang-kaling’ jam. Materials and Methods: A factorial design with a completely randomized design that considered 2 factors was used. Factor A was addition of ‘jamblang’ peel, at four concentrations: A1 (10%), A2 (15%), A3 (20%) and A4 (25%) and factor B was the addition of citric acid at three concentrations: B1 (0.2 g), B2 (0.3 g) and B3 (0.4 g). ‘Kolang-kaling’ jam with the various additions was analyzed for total phenol and total anthocyanin content, as well as antioxidant activity (IC50). Results: The addition of ‘jamblang’ peel and citric acid significantly (p